(untitled) (Journal of the College of Languages (JCL), 2025)
This paper examines the influence of extreme capitalism within the pharmaceutical industry and the existence of sentient robots within the context of transhumanism in the American novel Autonomous (2017) by Annalee Newitz (1969- ). It also utilizes the theory of deontological ethics to clarify the ethical state of this futuristic world within the novel. Additionally, the application of virtue ethics is an attempt to select an ethical theory that aligns with the future of technological advancements. As technology rapidly progresses, resulting in extreme shifts in the ethical, political, and societal spheres, it becomes important to uphold ethical principles that would survive the test of time. Such ethical principles would be influential in cases where existing theories about ethics become insufficient in coping with the impact of ever-increasing technological progress. The paper also explores how Autonomous critiques the commodification of medicine by big pharma, as well as the ethics of merging man and machine against the backdrop of deontology. This is primarily accomplished by employing textual analysis to explore and contextualize the pharmaceutical company “Zaxy” within the deontological system of ethics. It also examines the events in Autonomous in relation to real-world circumstances and delves into the consequences that arose from the existence of sentient robots and how deontology would view those consequences, especially the extension of human rights to machines. In seeking to discover an ethical theory that holds value in the future, character analysis is done from the perspective of virtue ethics as a possible solution to the lack of certainty concerning the future of technological progress. The findings reveal that Autonomous reflects a common concern about transhumanism: its potential to amplify some negative aspects of capitalism. This is illustrated by the depiction of humans as a tool for profit, and by the limited access to new medicine, all of which are contradictory to the imperative of deontological ethics. The study concludes that character virtue serves as an anchor for proper ethical behavior in a future where the concept of ethics itself is redefined. However, balancing the demands of the drug patent system with the necessity to pursue the well-being of the public remains an unresolved ethical challenge.